RG7774 (Vicasinabin), an orally bioavailable cannabinoid receptor 2 (CB2R) agonist, decreases retinal vascular permeability, leukocyte adhesion, and ocular inflammation in animal models - Grether, Uwe; Foxton, Richard H.; Gruener, Sabine; Korn, Claudia; Kimbara, Atsushi; Osterwald, Anja; Zirwes, Elisabeth; Uhles, Sabine; Thoele, Janina; Colé, Nadine; Rogers-Evans, Mark; Röver, Stephan; et al. (Frontiers in Pharmacology, 2024)
First-line pharmacotherapy for diabetic retinopathy (DR) includes regular intravitreal injections with anti-vascular endothelial growth factor (anti-VEGF) therapies. Although effective, intravitreal anti-VEGF injections are highly invasive, and are associated with a high degree of treatment burden, patient anxiety, and an infrequent but serious risk of intraocular inflammation. This preclinical proof-of-concept study shows that RG7774 is a novel, highly selective, and orally bioavailable cannabinoid 2 receptor (CB2R) agonist, with a favorable systemic and ocular pharmacokinetic profile, and beneficial effects on vascular permeability, leukocyte adhesion, and ocular inflammation (key pathological features of DR) in animal models of retinal disease. Results support the development of RG7774 as a potential noninvasive treatment for DR and other retinal diseases with similar pathophysiology.